The hidden impacts: Identifying psychological burdens during the Covid-19 pandemic - Nurdiyanto, F A; Harjanti, Enggar Putri (Indigenous, 2022)
Abstract. The COVID-19 pandemic has increased the complexity of mental health issues and burdens. Psychological problems also arise as a domino effect of the massive crisis of the pandemic. Various studies and rapid assessments have been carried out and confirmed the alleged increase in psychological problems. However, identifying the psychological burdens that arise during the pandemic has not been explored qualitatively. For this reason, this study was conducted to identify the psychological burdens that arise during a pandemic to understand how the COVID-19 pandemic affects mental health. This study used an exploratory qualitative approachby collecting data through online open-ended questions. Seven hundred and four people (462 women; x̄ age of 27.06 years) participated by purposive technique. Thematic analysis was applied to identify and analyze patterns of meaning perceived as psychological burdens during the pandemic. The study found five themes: stress related to the pandemic, anxiety, depression, emotional instability, and loneliness. This research encourages efforts to anticipate increased mental health problems when dealing with a pandemic and provide access to psychological assistance for vulnerable groups.Keywords: psychological burdens; Covid-19 pandemic; thematic analysis.